PENGARUH PENERAPAN LEMBAR KERJA PESERTA DIDIK BEBRBASIS PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK KELAS VIII SMPN 2 PARIAMAN - HAMIDAH . (Jurnal Edukasi dan Penelitian Matematika, 2020)
Based on observation at class VIII SMPN 2 Pariaman, it was found that students’ mathematical reasoning abilities were low. One of the reasons is students are accustomed to working on the questions in accordance with the examples of the questions given and the learning used is less able to improve their reasoning abilities. Efforts that can be used are implementing  students based on scientific approach. The purpose of this study is to determine and describe whether the ability of mathematical reasoning learning with the application of students based on scientific approach is better than the ability to solve mathematical reasoning with learning does not use student worksheets based on a scientific approach. This type of research is quasy experimental research design with Randomized Static Group Design. The study population was students of class VIII SMPN 2 Pariaman with a sample of VIII.4 chosen as experimental class VIII.5 as the control class. The instruments used were quizzes and tests of mathematical reasoning abilities. The results showed the ability to solve mathematical reasoning with the application of students based on scientific approach of is better than the ability to solve mathematical reasoning with learning does not use student worksheets based on a scientific approach.Keywords–student worksheets based on a scientific approach, reasoning skill, Mathematics,